2020
DOI: 10.3390/molecules25051161
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Encapsulation, Protection, and Oral Delivery of Bioactive Proteins and Peptides using Colloidal Systems

Abstract: There are many areas in medicine and industry where it would be advantageous to orally deliver bioactive proteins and peptides (BPPs), including ACE inhibitors, antimicrobials, antioxidants, hormones, enzymes, and vaccines. A major challenge in this area is that many BPPs degrade during storage of the product or during passage through the human gut, thereby losing their activity. Moreover, many BPPs have undesirable taste profiles (such as bitterness or astringency), which makes them unpleasant to consume. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 184 publications
(234 reference statements)
0
56
0
1
Order By: Relevance
“…Additionally, they should not modify the physicochemical and organoleptic properties of the peptide-based food products. Finally, because of the high demand by consumers of “clean-label” food products, carriers manufactures are limited to the use of natural ingredients and biodegradable, generally recognized as safe (GRAS) alternatives [ 209 , 210 ]. This has made it much more difficult to produce food-based delivery systems with the required functional attributes.…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they should not modify the physicochemical and organoleptic properties of the peptide-based food products. Finally, because of the high demand by consumers of “clean-label” food products, carriers manufactures are limited to the use of natural ingredients and biodegradable, generally recognized as safe (GRAS) alternatives [ 209 , 210 ]. This has made it much more difficult to produce food-based delivery systems with the required functional attributes.…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
“…This has made it much more difficult to produce food-based delivery systems with the required functional attributes. Therefore, the design of the most suitable delivery systems requires extensive knowledge of the physicochemical and molecular attributes of bioactive peptides (molecular dimmension, electrostatic effects, polarity, solubility, and surface activity) as well as the environmental factors, ingredients interactions, and digestive conditions that can negatively alter the structure and bioactivity of peptides [ 210 , 211 ]. The most recent delivery systems applied for the encapsulation of food bioactive proteins and/or peptides and the effects on their stability, bioavailability, and bioactivity are summarized in Table 3 .…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
“…Several methods for peptides encapsulation are spray drying (Wang & Selomulya, 2020), colloidal (Perry & McClements, 2020), coacervation (Mohan et al, 2015), cold-set gelation (O'Neill et al, 2014), extrusion (de Vos et al, 2010), and electrospinning (Wen et al, 2017). Spray drying is done by suspending BPs in polymer carriers such as maltodextrin, starch, or gum arabic, and the mixture is sprayed through an atomizer in which the liquid evaporates and thereby resulting in a powder form (Wang & Selomulya, 2020).…”
Section: Future Develop-ment/outlook/challengesmentioning
confidence: 99%
“…Colloidal encapsulation involves the mixing of two immiscible phases to produce a stable emulsion barrier such as single emulsion, double emulsion, Pickering's emulsion, liposomes, solid particles, microgels, and microemulsion (Perry & McClements, 2020). It was reported that less hydrophobic oils have higher peptide release under simulated gastrointestinal conditions, suggesting that peptide release from emulsion occurred through two mechanisms, that is, diffusion across oil phase and lipolytic degradation (Giroux et al., 2016).…”
Section: Future Development/outlook/challengesmentioning
confidence: 99%
“…Permeation enhancers substances can increase the absorption of encapsulated biological active compounds in the gastrointestinal tract. One of the mechanisms of this action is opening the tight junctions of the epithelium cells [73,74]. Chitosan has a mucoadhesive nature and capable to open epithelial connections (tight junctions) of the epithelium cells [75,76].…”
Section: Chitinmentioning
confidence: 99%